Design Of A Budget Processing Information System At Sat Reskrim Of Polres Labuhanbatu Web Based - Martasya Berkat Silaen, Dian; Juni Yanris, Gomal; Nirmala Sari Hasibuan, Mila; Rohayani Hasibuan, Elysa (Publisher Cv. Inara, 2024)
Capital expenditures carried out by regional governments produce infrastructure in an area both for providing basic services to the community and to encourage regional governments to provide potential sources of local revenue. The Financial Report of the National Police of the Republic of Indonesia consists of a budget realization report, balance sheet, operational report, report on changes in equity and notes on the financial report as attached, which is the responsibility of the National Police which has been prepared based on an adequate internal control system. The aim of this research is to be able to design an information system for processing budget data to unit of Sat Reskrim the Polres Labuhanbatu is web-based so that it can help operational work, especially in processing financial data, to be more effective and efficient